A joint water diversion plan for China. Issue 5 (1st May 2013) - Liang, Shumin
Abstract : To achieve domestic food security and help alleviate poverty, China is undertaking ambitious water transfer projects as a means of optimizing management of its water resources. This article proposes a three‐part approach to south‐to‐north water diversion in China. The plan consists of an extension to the current middle route, an alternative (and expanded) western route, and a trunk canal system to transfer water to the northwest. The proposed project would be undertaken in four stages; costs and benefits of each stage are included here. With the completion of the plan, the total annual capacity of south‐to‐north water diversion in China would be 238 × 10 9 m 3 . Total project investment is estimated at 3, 147 billion yuan ($498 billion). Major benefits generated by the project include annual income of 287 billion yuan ($45 billion) through sales of water and hydropower, addition of 44.3 × 10 6 ha (109 × 10 6 acres) of irrigated arable land, relocation of 66.5 × 10 6 inhabitants to newly irrigated regions, and conversion of 470, 000 km 2 (181, 468 sq mi) of desert to irrigated land and forest to provide wind shelter and preserve topsoil.